Polymer bioadhesives for drug delivery - Deacon, Matthew (1999)
This study is a natural follow on from previous work by M. T. Anderson and I. Fiebrig. The goal of those latter and of the present study is to find a mucoadhesive system for improving the oral bioavailability of a number of drugs, for example bioactive peptides and proteins. This current work evaluates the adhesive properties of a cationic polymer and a cationic protein to mucus glycoproteins as a step towards the future development of a mucoadhesive drug delivery system. Four different mucin populations were analysed in solution (a freshly purified sample PGM-MD, and three purified from different regions of the porcine stomach cardiac, antrum and fundus). Their interaction with two groups of chitosans differing in degree of deacetylation (FA = 0.11 and 0.25) and a protein purified from the foot of the blue mussel Mytilus edulis foot protein-1 (Mefp-1) were studied. Interaction was determined using analytical ultracentrifugation and with the chitosan/mucin interaction specifically atomic force microscopy. The influence of ionic strength on the interaction was studied in detail studied as was the effect of the oligosaccharide composition of the mucin population on the interaction. It was found that both groups of chitosans (FA = 0.11 and 0.25) formed a large complex with a freshly purified mucin population (PGM-MD). Ionic strengths above 0.2 M were found to inhibit the interaction. The three mucin species differed in terms of their net charge, with cardiac being the most negatively charged and antrum the least negative. It was found that the cardiac species interacted the most and antrum the least, as would be expected for an ionic interaction. Increasing ionic strength was found to inhibit the interaction. There was also evidence for a hydrophobic interaction at high ionic strengths. The atomic force microscopy results allowed the complex to be visualised under atmospheric conditions and to get away from the harsh sample preparation techniques employed by electron microscopy. Large spherical complexes were seen as entanglements of mucin and chitosan strands.